Chemical Additives for Gas Hydrates - Lal, Bhajan; Nashed, Omar.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book offers a straightforward, informative guide to the chemicals used for gas hydrate formation and inhibition, providing the reader with the latest information on the definition, structure, formation conditions, problems, and applications of gas hydrates. The authors review not only the inhibitors used to prevent or mitigate hydrate formation, but also the conditions under which it is necessary to form hydrates quickly, which require the use of promoters. Various promoters are discussed, including their specifications, functions, advantages and disadvantages. The possibility of using natural reservoirs of gas hydrate as an energy source is also considered. Lastly, due to the difficulty of conducting experiments that reflect all conditions and concentrations, the book presents a number of models that can predict the basic parameters in the presence of the chemicals. Given its scope, the book will be of interest to professionals working in this field in an industrial context, as well as to researchers, undergraduate and graduate students of chemical engineering. .
Introduction to Gas Hydrates -- Gas Hydrates Inhibitors -- Gas Hydrates Promoters -- Gas Hydrates Models.
Keywords: Fossil fuels; Chemical engineering; Fossil Fuels (incl. Carbon Capture).; Industrial Chemistry/Chemical Engineering